Sonovoltammetric measurement of the rates of electrode processes with fast coupled homogeneous kinetics: Making macroelectrodes behave like microelectrodes - Compton, R; Marken, F; Rebbitt, T (1996)
Voltammetric measurements of the rates of fast homogeneous chemical reactions coupled to heterogeneous electron transfer at macroelectrodes are demonstrated for two systems, the reductive dehalogenations of ortho-bromonitrobenzene and of 3-bromobenzophenone, by the use of power ultrasound to confer fast mass-transport properties so giving the electrodes the kinetic timescale of microelectrodes.